Medication Adherence and Persistence of Open-Angle Glaucoma Patients in Korea: A Retrospective Study Using National Health Insurance Claims Data - Jang, Yunjeong (Int J Environ Res Public Health, 2021)
This study aimed to analyze medication adherence and persistence among open-angle glaucoma patients in Korea. A retrospective study was conducted using the Korean National Health Insurance (NHI) claims database from 2016 to 2019. Newly diagnosed open-angle glaucoma patients who were prescribed with the intraocular pressure (IOP)-lowering eyedrops were included. Adherence was measured using the medication possession ratio (MPR), and persistence was measured using the duration of therapy during the 24 month follow-up period. During the study period, 14,648 open-angle glaucoma patients were identified, and 3118 (21.3%) and 4481 patients (30.6%) were adherent to and persistent with their glaucoma treatment, respectively. The mean MPR was 48.8%, and the mean duration of therapy was 357.2 days. Logistic regression analysis showed that patients who are older, female, using prostaglandins as the index medication, and visiting secondary or tertiary hospitals were significantly associated with greater rates of adherence (odds ratio (OR) = 1.21, 1.12, 1.27, and 1.73, respectively) and persistence (OR = 1.11, 1.17, 1.16, 1.17, and 1.36, respectively) during the study period. Patients with open-angle glaucoma in Korea had substandard medication adherence and discontinued their treatment. Ophthalmologists should pay more attention to younger, male patients to improve adherence.